Children retain implicitly learned phonological sequences better than adults: a longitudinal study. Issue 5 (17th December 2017) - Smalle, Eleonore H.M.; Page, Mike P.A.; Duyck, Wouter; Edwards, Martin; Szmalec, Arnaud
Abstract: Whereas adults often rely on explicit memory, children appear to excel in implicit memory, which plays an important role in the acquisition of various cognitive skills, such as those involved in language. The current study aimed to test the assertion of an age‐dependent shift in implicit versus explicit learning within a theoretical framework that explains the link between implicit sequence memory and word‐form acquisition, using the Hebb repetition paradigm. We conducted a one‐year, multiple‐session longitudinal study in which we presented auditory sequences of syllables, co‐presented with pictures of aliens, for immediate serial recall by a group of children (8–9 years) and by an adult group. The repetition of one Hebb sequence was explicitly announced, while the repetition of another Hebb sequence was unannounced and, therefore, implicit. Despite their overall inferior recall performance, the children showed better offline retention of the implicit Hebb sequence, compared with adults who showed a significant decrement across the delays. Adults had gained more explicit knowledge of the implicit sequence than children, but this could not explain the age‐dependent decline in the delayed memory for it. There was no significant age‐effect for delayed memory of the explicit Hebb sequence, with both age groups showing retention. Overall performance by adults was positively correlated with measures of post‐learning awareness. Performance by children was positively correlated with vocabulary knowledge. We conclude that children outperform adults in the retention over time of implicitly learned phonological sequences that will gradually consolidate into novel word‐forms. The findings are discussed in the light of maturational differences for implicit versus explicit memory systems that also play a role in language acquisition. A video abstract of this article can be viewed at: https://youtu.be/G5nOfJB72t4 Abstract : Eight‐ to nine‐year‐old children outperform adults in the retention over time of implicitly learned syllable sequences; and this up to a delay of one year. Adults gain more explicit knowledge of the sequences. This does not explain the age‐dependent decline in delayed memory for it. The findings support the hypothesis that children outperform adults in their use of implicit‐learning mechanisms related to language.